KOMPLIKASI NEUROLOGI PADA INFEKSI HIV - Kiking Ritarwan* (NEURONA, 2011)
INTRODUCTION HIV VIRUSES ARE INCLUDED OF RNA GROUP OF RETROVIRUS FAMILY AND LENTIVIRIDAE SUBFAMILY HIV INFECTION IS PANDEMIC IN THE WORLD THAT AFFECT ALL GROUP OF POPULATION ESPECIALLY SPREAD RAPIDLY IN THE DEVELOPING COUNTRIES THE INVOLVEMENT OF NEURAL SYSTEM IN HIV INFECTIONS CAN BE DIRECT OR DUE TO OPPORTUNISTIC INFECTION BECAUSE IMMUNOCOMPROMISED STATUS THE RECENTLY ARE TENDENCY OF INCREASING NUMBER OF HIV PATIENTS WITH OPPORTUNISTIC THE HAART TREATMENTS DECLINE VIRAL LOAD IN BLOOD AND THEREFORE DECREASE MORTALITY RATE AND INCREASE LIFE EXPECTANCY RATE